The Shifting Development Paradigm from Modernization to Decentralization: What are the implications for Adult Education? - Rosemary B. Closson; Paul Mavima; Kofi Siabi-Mensah (Adult Education Research Conference, 1999)
This research explored emerging patterns of providership for nonformal education programs in Ghana, Senegal, and Burkina Faso where each country is in various stages of decentralization and democratization. The study found that, increasingly, multiple actors are responsible for nonformal education activities and that, unfortunately, though this could raise the profile of adult education it actually may further obscure its role.